Reflecting Phased Array Antenna Consisting of Rectangular Waveguides of Finite Depth - Gribovsky, A. V.; Prosvirnin, S. L.; Reznik, I. I. (Видавничий дім «Академперіодика», 2012)
Reflecting Phased Array Antenna Consisting of Rectangular Waveguides of Finite Depth